2022
DOI: 10.1155/2022/7563281
|View full text |Cite|
|
Sign up to set email alerts
|

Liraglutide Is Protective against Brain Injury in Mice with Febrile Seizures by Inhibiting Inflammatory Factors

Abstract: The febrile seizure (FS) is a common disease in emergency pediatrics, and about 30% of patients are children aged between 6 months and 5 years. Therefore, we aim to observe the protective impact of liraglutide (LIR) on brain injury in mice with FS and to explore its relevant mechanisms. Male SD mice were selected, and the FS model was established by heat bath method. The behavioral score was performed on mice with Racine grading, and nerve cells in apoptosis in the hippocampus were determined by TUNEL. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
2
0
3
Order By: Relevance
“…Estão dispostos na tabela 1 mais detalhes sobre os dados obtidos. De acordo com Wang et al (2022), as convulsões febris, que acontecem com certa frequência durante a infância, principalmente entre as idades de 6 meses e 5 anos, são decorrentes de uma interação complexa de fatores genéticos, processos imunoinflamatórios e ativação da rede de citocinas. Caso tal enfermidade ocorra de forma crônica, cerca de 7% das crianças podem apresentar complicações, como a epilepsia pré-púbere com lesão neuronal grave.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Estão dispostos na tabela 1 mais detalhes sobre os dados obtidos. De acordo com Wang et al (2022), as convulsões febris, que acontecem com certa frequência durante a infância, principalmente entre as idades de 6 meses e 5 anos, são decorrentes de uma interação complexa de fatores genéticos, processos imunoinflamatórios e ativação da rede de citocinas. Caso tal enfermidade ocorra de forma crônica, cerca de 7% das crianças podem apresentar complicações, como a epilepsia pré-púbere com lesão neuronal grave.…”
Section: Resultsunclassified
“…Descrição dos resultados obtidos para a composição do trabalho et al (2022); EILBERT;CHAN, 2022;JAIN;SANTHOSH, 2021;WANG et al (2022);RAGHAVAN et al (2021).…”
unclassified
“…Нокдаун экспрессии GLP1R в alBST продлевает реакцию гипоталамо-гипофизарно-надпочечниковой оси на острый стресс. Учитывая данные о том, что ГАМК-ергическая проекция от вентрального alBST служит для ограничения реакции индуцированной стрессом оси гипоталамус-гипофиз-надпочечники, можно предположить, что передача сигналов ГПП-1 приводит к активации ГАМК-ергических вентральных нейронов alBST, которые проецируются непосредственно в паравентрикулярное ядро гипоталамуса (PVN) [ 20 ][ 32 ][ 35 ][ 36 ]. Эти данные раскрывают механизм взаимодействия ГПП-1Р и ГАМК, посредством которых alBST осуществляет ингибирующий контроль над эндокринной осью гипоталамус-гипофиз-надпочечники.…”
Section: класс-специфические свойства агонистов рецепторов гпп-1 и ин...unclassified
“…Computational and Mathematical Methods in Medicine has retracted the article titled “Liraglutide Is Protective against Brain Injury in Mice with Febrile Seizures by Inhibiting Inflammatory Factors” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine has retracted the article titled "Liraglutide Is Protective against Brain Injury in Mice with Febrile Seizures by Inhibiting Inflammatory Factors" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%